Delayed interval delivary in multiple gestation - ULUDAĞ, Seyfettin; GEZER, Altay; KOŞCAĞIZ CANSEVER, İrem and DURU SUİÇMEZ, Banu (Cerrahpaşa Medical Journal, 2014)
Triplet pregnancy at 16 weeks gestational age referred to outpatient clinic with the complaint of premature rupture of membranes. At 18 weeks of pregnancy, the presenting fetus was delivered vaginally and parenteral ritodrin tocolysis was initiated. At 21 weeks of gestation, cervical cerclage procedure (Shirodkar) was performed. Followed by parenteral tocolysis up to 34 weeks of pregnancy, the birth of remaining twins was accomplished by cesarean section. Delayed interval delivery certainly improves fetal well-being and outcome. Different therapy strategies could be utilized for this purpose. Bed rest, continuous or intermittent hospitalization, tocolysis, antibiotic therapy, corticosteroid administration over 26 weeks and cervical cerclage are the main alternatives in the management.